The weathering action of saxicolous lichens in maritime Antarctica - Ascaso, Carmen; Sancho, Leopoldo G.; Rodríguez Pascual, C. (1990)
7 pages, figures and tables statistics. Xanthoria elegans (Link) Th Fr. and Lecidea lapicida (Ach.) were studied on volcanic andesite, and Rhizocarpon geooraphicum (L.) DC. and Bacidia stipata Lamb on a volcanigenic sediment, using light microscopy, infrared spectroscopy, X-ray diffraction and transmission electron microscopy. Feldspars were present in the rocklichen interface to a lesser extent than in the underlying rock. R. geographicum was found to alter the minerals in the rock on which it grew without producing any new minerals in the rock/lichen interface, in contrast to the observations for this species on granite in temperate regions. Beneath of the thallus of L. lapicida there was calcium oxalate and some micas of the illite type, which may have been degradation products of various phyllosilicates in the rock. B. stipata, an endemic Antarctic lichen, had the greatest capacity to weather the rock and had weddellite (dihydrate calcium oxalate) and calcite in the contact area as well as many bacteria. The presence of crystalline oxalate, imogolite, allophane, carbonates (calcite) and amorphous material not found in the parent rock indicates biomineralization processes attributable to the lichens. We are pleased to acknowledge that this work was supported by a grant number PB87 0229 from the Comisi6n Asesora de Ciencia y Tecnologia. We are grateful to Mr. F. Pinto and M. T. Carnota for technical assistance, and to Prof. Kappen and William Sanders for help with the English manuscript. Peer reviewed